2D laser lithography on silicon substrates via photoinduced copper-mediated radical polymerization. Issue 7 (8th January 2018) - Laun, Joachim; De Smet, Yana; Van de Reydt, Emma; Krivcov, Alexander; Trouillet, Vanessa; Welle, Alexander; Möbius, Hildegard; Barner-Kowollik, Christopher; Junkers, Tanja
Abstract : A 2D laser lithography protocol for controlled grafting of polymer brushes in a single-step is presented. Abstract : A 2D laser lithography protocol for controlled grafting of polymer brushes in a single-step is presented. A series of polyacrylates were grafted from silicon substrates via laser-induced copper-mediated radical polymerization. Film thicknesses up to 39 nm were reached within 125 μs of exposure to UV laser light (351 nm). Successful block copolymerization underpinned the controlled nature of the grafting methodology. The resolution of a small structure of grafted PHEA reached 270 μm and was limited by the type of laser used in the study. Further, a checkerboard pattern of PtBA and POEGA was produced and imaged via time-of-flight secondary ion mass spectrometry (ToF-SIMS), and X-ray photoelectron spectroscopy (XPS).